1997
DOI: 10.1097/00042560-199701010-00007
|View full text |Cite
|
Sign up to set email alerts
|

Insurance Type and Satisfaction with Medical Care Among HIV-Infected Men

Abstract: Patient satisfaction is a valuable indicator of the quality of medical care. We assessed the impact of type of health insurance on satisfaction with seven aspects of medical care among 593 HIV-infected men without AIDS, drawn from three sites in San Francisco, California and Denver, Colorado. After adjustment for site of medical care, patient age, race, income, education, and CD4 lymphocyte count, there were few differences in satisfaction between men with fee-for-service and those with managed care insurance.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…While some patient characteristics were associated with dissatisfaction across multiple dimensions, other characteristics were associated only with certain domains, supporting the idea that the salience of each dimension is neither uniformly nor randomly distributed through the population (Thomas & Penchansky, 1984). For example, while the finding that women with private insurance were more dissatisfied with financial aspects of health care than those with public or no insurance may seem counterintuitive, it is supported by a study of HIV-infected men that found that those with private, fee-for-service insurance were less satisfied with financial aspects of care than others (Katz et al ., 1997). This dissatisfaction may be the result of expenses incurred through co-payments or deductibles, and suggests that providers should examine the degree of financial burden experienced by those with private insurance who are typically thought to be at an advantage economically.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While some patient characteristics were associated with dissatisfaction across multiple dimensions, other characteristics were associated only with certain domains, supporting the idea that the salience of each dimension is neither uniformly nor randomly distributed through the population (Thomas & Penchansky, 1984). For example, while the finding that women with private insurance were more dissatisfied with financial aspects of health care than those with public or no insurance may seem counterintuitive, it is supported by a study of HIV-infected men that found that those with private, fee-for-service insurance were less satisfied with financial aspects of care than others (Katz et al ., 1997). This dissatisfaction may be the result of expenses incurred through co-payments or deductibles, and suggests that providers should examine the degree of financial burden experienced by those with private insurance who are typically thought to be at an advantage economically.…”
Section: Discussionmentioning
confidence: 99%
“…This instrument has been used in numerous studies supporting its validity and reliability in a variety of patient populations (Harris et al ., 1995;Maly et al ., 1998;Pascoe, 1983;Roberts & Tugwell, 1987;Ross et al ., 1995;Sutcliffe et al ., 1999), including people with HIV/AIDS (Katz et al ., 1997;Stein et al ., 1993). The measure captures seven dimensions of patient satisfaction: general satisfaction; technical quality; interpersonal manner; communication; financial aspects; time spent with provider; and accessibility/convenience.…”
Section: Satisfaction Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on prior studies9,14,18,19 and data available in WIHS, the following visit-specific time-varying variables (unless otherwise stated) were selected as predictors for CAM disclosure: (1) sociodemographic characteristics included age in years (<35, 35–45 and >45), racial/ethnic identification (non-Hispanic Black, non-Hispanic White, Hispanic and others), and educational level (less than high school, some high school, or college and above) at study index visit, as well as annual income (>$12,000 or not), employment status, and any medical insurance coverage at each visit; (2) health care utilization indicators included number of health care provider visits (<2, 2–3, 4–5, and 6+), any hospitalization, number of CAM domains (1, 2, 3, and 4) and different type of CAM domain used since last visit; (3) functional status of participants consisted of depressive symptoms (measured by using the Center for Epidemiologic Studies Depression Scale [CESD],20 with a score 16 or higher defined as depression) and overall health-related quality of life (QOL, measured on a scale from 0 to 100 using a modified version of the MOS-HIV21 and was categorized using tertiles); (4) patient satisfaction was evaluated using the RAND Patient Satisfaction Questionnaire Short Form (PSQ-18), which has demonstrated validity and reliability among individuals with HIV/AIDS 22,23. We used the general satisfaction domain (categorized by quartiles) of this instrument to represent participants’ overall satisfaction with health care received; (5) clinical variables included CD4 + T cell counts (measured using standardized three or four color flow cytometry24), HIV RNA level (measured using the isothermal nucleic acid sequence based amplification method [bioMérieux, Boxtel, NL]), number of HIV-related symptoms (including fever, memory/concentration problem, diarrhea, numbness/tingling/burning rash, unintentional weights loss, difficulty with mental tasks, drenching night sweats, and divided into four categories 0, 1, 2, >2), clinical AIDS diagnosis (1993 criteria25), as well as use of antiretroviral therapy (no therapy, non-HAART therapy, and HAART).…”
Section: Methodsmentioning
confidence: 99%
“…Likewise, patients' trust in their physicians is higher in fee-forservice indemnity plans than in capitated or fee-for-service managedcare plans, 23 and studies have suggested that individual patients are more satisfied with the care they receive in private practice. [30][31][32][33][34] Although I do not believe that we have lost the essential elements of "doctoring" as yet, these trends are disturbing.…”
Section: Threats To the Patient-physician Relationshipmentioning
confidence: 99%